2022
DOI: 10.1001/jamanetworkopen.2022.15513
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Difference of Noninvasive Blood Pressure Measurements by Sex and Height

Abstract: Key Points Question Do noninvasive brachial cuff blood pressure (BP) measurements accurately estimate the invasive aortic (or true) BP in men and women? Findings In this cross-sectional study of 500 patients undergoing cardiac catheterization at a tertiary care academic hospital, women had significantly higher invasively measured aortic systolic BP (SBP) compared with men with similar brachial cuff SBP. This disparity was mostly explained by a difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Hypotheses such as smaller vessel caliber or more pronounced aging-related loss of compliance have been proposed to explain this association ( 33 , 34 ). As such, our team has recently shown that female sex is associated with a greater inaccuracy of brachial cuff, C1SBP for AoSBP while male sex is associated with greater inaccuracy of C2SBP for predicting AoSBP ( 20 , 21 ). As expected, we obtained similar findings in this study using the same cohort.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hypotheses such as smaller vessel caliber or more pronounced aging-related loss of compliance have been proposed to explain this association ( 33 , 34 ). As such, our team has recently shown that female sex is associated with a greater inaccuracy of brachial cuff, C1SBP for AoSBP while male sex is associated with greater inaccuracy of C2SBP for predicting AoSBP ( 20 , 21 ). As expected, we obtained similar findings in this study using the same cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Although the inaccuracy between central BP and the true aortic SBP was traditionally attributed to errors in the measurement of brachial cuff BP, recent studies conducted by our group have shown that several clinical characteristics (notably female sex and height) influenced the accuracy between non-invasive and invasive brachial BP (20,21). Since central BP measurements are highly dependent on an accurate brachial cuff BP for calibration, we hypothesized that adjusting for such clinical parameters could enhance the performance of central BP devices.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, there are differences between women and men in standard upperarm cuff measured BP. However, there is emerging data that cuff BP measurements may be more inaccurate in women compared with men [78]. Two recent studies have found that for the same cuff systolic BP, invasive aortic systolic BP was significantly higher in women, but not men [78,79].…”
Section: Pressure and Flow Waveform Physiologymentioning
confidence: 99%
“…However, we are only in the beginning stages of understanding how physiologic measures, such as brachial BP, may also benefit from sex-specific considerations. In this study, Abbaoui et al press us to question even further the method of a physiologic measurement and its potentially limited generalizability across sexes. In effect, we are now challenged to ask whether we have been using the correct device, the correct device settings, or the correct units or reference ranges when performing a particular physiologic measure given what we know about fundamental sex differences in anatomy and the interdependence between anatomy and physiology.…”
mentioning
confidence: 97%
“…In JAMA Network Open, Abbaoui et al 3 have taken on the important task of clarifying how observed sex differences in peripherally measured systolic BP (SBP) and related outcomes may, in fact, be related to a discordance in how well the brachial cuff pressure reflects central BP. In a cohort of 500 patients with a mean (SD) age of 66 (10) years who were referred for coronary angiography, including 145 women (29%), postprocedural, catheter-based measurements of ascending aortic and intrabrachial pressures were recorded in sync with noninvasive central and brachial pressures assessed using an automatic BP monitor (Mobil-O-Graph; I.E.M.).…”
mentioning
confidence: 99%